Socio-Cultural Status of Gadvi Walay: An Anthropological Study of Gadvi Walay in Kallur Kot, Bhakkar Pakistan - Yousaf, Anum; Malik, Muhammad Yasir; Shakir, Muhammad; Jamil, Tehmina (Pakistan Journal of Humanities and Social Sciences, 2023)
Music is necessary for life. Music is important at every stage of marriage ceremonies. The major focus of the resent research was on Socio-cultural status of Gadvi walay. Research does to know about the cultural significance of gadvi walay’s community. The study finds out the causative factors behind the adoption of folk music as well as knows about the role and status of women to perform these traditional musical patterns and find out the factors of decline of folk music. The marriage ceremonies are color less without traditional entertainer such as “Gadvi walay” and “Dhol walay” (Musician). The recent study was conducted to evaluate the status of “Merrasi” (Traditional Singers) community. This community perform vital role in the marriage and other cultural events. This study was conducted in the rural area of district Bhakhar. The one of union council was selected from the tehsil of kallur Kot. While applying purposive sampling technique, the thirty female respondents were selected (gadvi walay from the local community. Participant observation, Interview guide and in-depth interview methods were used for the data collection. The present study explained the role, status and significance of traditional folk music, musicians songs and singers in their cultural perspective.